Phenomenon of Professional Stress in Pedagogical Activities of the Higher Education System - Razikova Lola Tuychiyevna (International Journal of Scientific Trends, 2024)
The article describes professional stress in pedagogical work and its effect on the work of a pedagogue. It is shown that a teacher's professional activity is accompanied by many stress factors that determine professional stress and have a negative effect on the effectiveness of the professional activity of teachers. It is noted that the violation of adaptive mechanisms, low resistance to stress, long-term chronic effects of stress factors lead to a number of psychosomatic diseases.